Initial growth stages of heavily boron‐doped HFCVD diamond for electrical probe application. Issue 10 (6th August 2013) - Simon, D. K.; Tsigkourakos, M.; Hantschel, T.; Conard, T.; Vandervorst, W.
<x xml:space="preserve">Abstract</x> The initial growth stages of boron‐doped diamond, deposited by hot‐filament chemical vapour deposition (HFCVD), are crucial for the conductivity of moulded tips used in scanning spreading resistance microscopy (SSRM) where the first grown layer is the active layer of the tip. In this paper, we investigate therefore the beginning of the growth by interrupting the HFCVD process for nano‐crystalline (NCD) and microcrystalline diamond (MCD) films at various moments during the filament carburisation. The characterisation of these initial stages is done by X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). A slow growth start after the first ∼20 min of carburisation is revealed by the change of C‐bindings at the seed surface towards pure CC indicated by XPS. AFM measurements show that the actual growth starts after ∼40 min. Our work shows that boron tends to form BO clusters at the beginning of the growth (∼50 min) which can affect the conductivity of the first layers of our tips. By using carburised filaments the diamond seeds form earlier more pronounced crystal shapes which are related to a higher sp3/sp2 ratio. This is advantageous for moulded diamond tips used in electrical probing.